Salivary analysis of alpha-amylase and cortisol as pain markers in patients using conventional fixed orthodontic appliances and aesthetic aligners: Literature review (Research, Society and Development, 2024)
Malocclusions and dentofacial disharmonies are potential factors that have a negative impact on individuals' quality of life. In this sense, the search for a harmonious smile has been in evidence for thousands of years, with orthodontic treatment being a therapeutic alternative that provides function, stability and, consequently, dentofacial aesthetics. Aesthetic complaints during treatment have driven the industry to develop orthodontic aligners, a therapeutic alternative that modifies the biomechanics of tooth movement, with the main aim of reducing the visibility of the components of conventional fixed appliances. Just like aesthetics, orthodontic pain is one of the main side effects resulting from treatment, commonly reported by patients, regardless of the treatment modality chosen. Orthodontic pain can be measured using subjective methodologies, using verbal and/or visual scales, as well as objective methodologies, with the analysis of salivary biomarkers, such as alpha-amylase and cortisol. This literature review aims to compare the experience of orthodontic pain reported by individuals undergoing orthodontic treatment with conventional fixed appliances and orthodontic aligners, through the analysis of the salivary biomarkers’ cortisol and alpha amylase. For this purpose, scientific articles were selected from the following databases: PUBMED, LILAC’S, SCIELO and BVS, in Portuguese, Spanish and English. This literature review suggests that patients undergoing orthodontic treatment, both with conventional fixed appliances and orthodontic aligners, did not present differences in cortisol and alpha-amylase levels as salivary biomarkers of pain of orthodontic origin.